Artificial Intelligence in International Society: A Reappraisal of Realism, Rationalism, and Revolutionism - Iskandar, Monica Marchelina; Rasyida, Hamdan Nafiatur; Pradana, Hafid Adim (Journal of Transformative Governance and Social Justice, 2026)
This study analyzes the influence of Artificial Intelligence (AI) on the dynamics of the international order and its implications for inter-state relations and global governance, understood as the system of rules, norms, and institutions that regulate state behavior beyond national boundaries. The rapid adoption of AI has generated new challenges in security, economic competition, and international norms, defined as shared expectations that shape cooperation and restraint among states. This study employs a qualitative approach using literature review of academic journals, reports from international institutions, and policy documents. The data are analyzed through discourse analysis to identify patterns of state interaction, normative change, and emerging regulatory mechanisms related to AI development. The findings indicate that AI functions as a strategic tool that enhances state power while simultaneously deepening technological inequality between developed and developing countries. AI also challenges traditional notions of state sovereignty by blurring jurisdictional boundaries, complicating international law enforcement, and reshaping global governance arrangements. These dynamics highlight the need for a more adaptive and collaborative governance framework that balances national interests, global rules, and ethical principles. The study provides insights into how international society can manage AI in a more inclusive and sustainable manner amid evolving global power relations.